A novel genetic algorithm in LEACH-C routing protocol for sensor networks - Rahmanian, A.; Omranpour, H.; Akbari, M.; Raahemifar, K. (2011 24th Canadian Conference on Electrical and Computer Engineering(CCECE), 2011)
This paper presents a new approach to clustering wireless sensor networks and determining cluster heads. Here we apply evolutionary algorithms in centralized clustering. LEACH-C is one of the effective (basic) parameters in network life time based on energy consuming value protocol. In suggested evolutionary algorithm, through proper application of evolutionary operators, we search for efficient clustering based on each node's energy. Innovation of our method is in proper representation of chromosomes and also in determining proper fitness function according to problem features based on energy measure. In this paper we propose two new fitness functions. The results of applying these functions on four different types of sensor networks are presented and compared with the results of the Simulated Annealing method.